PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA CYBERBULLYING - Giawa, Yohanes Sarman (LPPM Universitas Nias Raya, 2025)
This research aims to determine legal protection for perpetrators of cyberbullying crimes. Normative legal research is the type of research used. One type of legal science known as normative law views the legal system as a system that uses and analyzes secondary data. Primary, secondary and tertiary data obtained from secondary legal texts are used in the data collection process. This research uses qualitative data analysis using descriptive methodology. Analyzing qualitative data involves examining well-gathered information without using numerical values. The findings of this study suggest that those who commit cyberbullying-related offenses may be eligible for legal protection. This is in accordance with Joint Decree Number 229 of 2021, 154 of 2021, and KB/2/VI/2021 of the Minister of Communication and Information of the Republic of Indonesia, as well as the Attorney General. National Police Chief regarding the implementation of special provisions in Law Number 11 of 2008 concerning Information and Electronic Transactions, as amended by Law Number 19 of 2016 concerning Law Number 11 of 2008 concerning Amendments to Law Number 11 of 2008 concerning Transactions the same one. Based on this ruling, not all nudity or pornography is offensive.